Characteristics of self-medication practice and associated factors among nursing undergraduate students - Flávio Martinez da Silva; Flávia Cristina Goulart; Carlos Alberto Lazarini (Universidade Federal de Goias, 2014)
The objective of this study was to characterize self-medication practice and associated factors among freshmen and senior nursing undergraduate students. Our approach was quali-quantitative and we gave a semi-structured questionnaire to all freshmen and senior undergraduate students. Quantitative data were analyzed using descriptive statistics and qualitative data, using the Discourse of the Collective Subject method. The results demonstrate that most first-year and all fourth-year students self-medicate. Furthermore, there were significant differences according to age group and the use of anti-inflammatory drugs between classes. The reasons that led students to self-medicate were: influence of others, pain relief, long waiting periods for receiving care, considering themselves in possession of enough scientific knowledge after taking a Pharmacology class. We concluded that self-medication is a common practice among students from both classes. After taking Pharmacology, seniors feel scientifically empowered enough for this practice. doi: 10.5216/ree.v16i3.20850.